2018
DOI: 10.3390/microorganisms6040107
|View full text |Cite
|
Sign up to set email alerts
|

Leaky Gut, Leaky Brain?

Abstract: ‘Leaky gut’ syndrome, long-associated with celiac disease, has attracted much attention in recent years and for decades, was widely known in complementary/alternative medicine circles. It is often described as an increase in the permeability of the intestinal mucosa, which could allow bacteria, toxic digestive metabolites, bacterial toxins, and small molecules to ‘leak’ into the bloodstream. Nervous system involvement with celiac disease is know to occur even at subclinical levels. Gluten and gluten sensitivit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
157
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 184 publications
(171 citation statements)
references
References 60 publications
(109 reference statements)
1
157
0
2
Order By: Relevance
“…These people may be exposed by risk of LPS. Recently, it has been reported that gut permeability is related to Alzheimer's disease, systemic lupus erythematosus, and allergic asthma (Obrenovich 2018;Costa et al 2016;Mu et al 2015;Farshchi et al 2017). Therefore, reducing intestinal hyper permeability could ameliorate not only food allergy but also other diseases.…”
Section: Discussionmentioning
confidence: 99%
“…These people may be exposed by risk of LPS. Recently, it has been reported that gut permeability is related to Alzheimer's disease, systemic lupus erythematosus, and allergic asthma (Obrenovich 2018;Costa et al 2016;Mu et al 2015;Farshchi et al 2017). Therefore, reducing intestinal hyper permeability could ameliorate not only food allergy but also other diseases.…”
Section: Discussionmentioning
confidence: 99%
“…Through the mucosal system and the interepithelial tight junctions, the GI tract continuously regulates trafficking of molecules between the host and the luminal environment. The gut blood barrier is an important component of gut function as it keeps potentially pathogenic bacteria and intestine-specific proteins from leaking out into circulating blood (Obrenovich, 2018). Emerging evidence suggests that gut permeability may precede many of the inflammatory events associated with disease (Arrieta et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…267,268 Increased gut permeability allows for bacteria, bacterial toxins, and LPS to enter the bloodstream and has been coined "leaky gut." 269,270 This leakiness is instigated by chronic inflammation and gut dysbiosis, which can contribute to systemic inflammation and the decreased BBB integrity associated with aging and AD. 229,269,271 BBB breakdown can ultimately lead to impaired removal of toxic species from the CNS and entry of pathogenic mediators from the periphery.…”
Section: Role Of Age Environmental Factors and Sex In Admentioning
confidence: 99%
“…269,270 This leakiness is instigated by chronic inflammation and gut dysbiosis, which can contribute to systemic inflammation and the decreased BBB integrity associated with aging and AD. 229,269,271 BBB breakdown can ultimately lead to impaired removal of toxic species from the CNS and entry of pathogenic mediators from the periphery. 269,271 Interestingly, compared with WT controls, APPPS1 mice have altered bacterial species in the gut, including higher levels of the bacteria B thetaiotaomicron.…”
Section: Role Of Age Environmental Factors and Sex In Admentioning
confidence: 99%
See 1 more Smart Citation